Pain Perception of the First Eye versus the Second Eye during Phacoemulsification under Local Anesthesia for Patients Going through Cataract Surgery: A Systematic Review and Meta-Analysis. (23rd June 2019) - Shi, Chuying; Yuan, Jinqiu; Zee, Benny
Abstract : Background. Phacoemulsification under local anesthesia is regarded as the major surgery for cataract treatment. Recent research has compared the pain perception between the first eye and the second eye during phacoemulsification. However, these studies have also yielded controversial findings. Consequently, we performed a systematic review and a meta-analysis to investigate the difference in the pain perception between the first and second eyes during phacoemulsification. Method . We searched the PubMed, EMBASE, and Cochrane CENTRAL databases for the studies published up to October 5, 2018. Prospective observational studies were included. The meta-analysis was conducted by means of random-effects model and fixed-effects model according to the heterogeneity. Evaluation of the methodological quality of studies was based on Newcastle-Ottawa Scale (NOS). Results . Overall, eight studies were included in the meta-analysis. The analysis of pooled data showed that the pain scores of the first eye shortly after surgery under local anesthesia were significantly lower as compared to the second eye (WMD: 0.69; 95% CI: 0.40, 0.98;P < 0.00001 ). The average pain scores of the first eye shortly after surgery under the topical anesthesia were also lower than those of the second eye (WMD: 1.08; 95% CI: 0.79, 1.36;P < 0.00001 ). Conversely, anxiety scores in the first eye surgery were significantly higher than those in the second eye surgery (SMD: −0.40; 95% CI: −0.64, −0.16;P = 0.001 ). However, the difference of the pain scores accessed on the first postoperative day between the first and second eye surgeries (WMD: −0.05; 95% CI −0.40, 0.31;P = 0.79 ) as well as cooperation grades of patients between the first and second eye surgeries (WMD: 0.35; 95% CI −0.07, 0.76;P = 0.10 ) was not statistically significant. Conclusion . Patients experienced more pain in the surgery of the second eye than that of the first eye, which probably related to lower anxiety before the second surgery. It suggests that we should consider preoperative intervention to reduce the perceived pain during second eye cataract surgery.